2007
DOI: 10.1111/j.1751-0813.2007.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of veterinary students and veterinarians: effects of growing up on a farm with animals

Abstract: In this study, veterinarians who had grown up on farms with animals seemed slightly more likely than those from other backgrounds to continue working in mixed practice and to work with cattle or sheep, although the numbers were small and the differences not significant. Whatever their background, the majority who started their careers in mixed practice left over the next few years, and by 15 years only 15% remained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Students selected for enrollment into professional veterinary curricula could also be selected on the basis of factors that would predispose them to having, and possibly maintaining, an interest in PH&E. Contrary to what might have been expected on the basis of other studies 17,28 in which predictors of careers in food animal production were investigated, the variables gender and rural upbringing were not associated with students in the present study having an interest in PH&E. The changing demographics of the veterinary profession may be unrelated to any perceived change in the interest level of students in careers related to PH&E. All but 1 veterinary student reported ownership of ≥ 1 animal prior to entry into veterinary school. Despite the high proportion of pet-owning students, ownership of several species in particular was a better predictor of an interest in PH&E. Students with prior ownership of farm animals were more likely to have a reported interest, and results of multivariable modeling suggested that in this population of students, raising cattle was the best predictor of an interest in PH&E.…”
Section: Proportion Of Students Proportion Of Students With Belief Andmentioning
confidence: 99%
“…Students selected for enrollment into professional veterinary curricula could also be selected on the basis of factors that would predispose them to having, and possibly maintaining, an interest in PH&E. Contrary to what might have been expected on the basis of other studies 17,28 in which predictors of careers in food animal production were investigated, the variables gender and rural upbringing were not associated with students in the present study having an interest in PH&E. The changing demographics of the veterinary profession may be unrelated to any perceived change in the interest level of students in careers related to PH&E. All but 1 veterinary student reported ownership of ≥ 1 animal prior to entry into veterinary school. Despite the high proportion of pet-owning students, ownership of several species in particular was a better predictor of an interest in PH&E. Students with prior ownership of farm animals were more likely to have a reported interest, and results of multivariable modeling suggested that in this population of students, raising cattle was the best predictor of an interest in PH&E.…”
Section: Proportion Of Students Proportion Of Students With Belief Andmentioning
confidence: 99%
“…A few were still in their first job, and a few, mainly employees, had held up to 10 jobs, some in private practice and some elsewhere. Although much has been made in management literature of the increasing rate of movement between jobs and careers and loss of employee loyalty in the community generally, 9,10 there is no clear evidence from this or other studies of the extent to which this applies in the veterinary profession.…”
Section: Discussionmentioning
confidence: 93%
“…The purpose of this paper is to provide a description and analysis of this information, especially the numbers engaged in various types of nonveterinary and veterinary work, the location of this work, the amount of work being done as a proportion of full time, and income. Another paper in this series focuses on gender and family issues, 9 and a third describes differences in career paths between those who grew up on a farm with animals and those from other backgrounds 10 …”
mentioning
confidence: 99%
“…This greater desire of Australian students to have daily contact with animals maybe explained by their greater involvement in keeping companion animals, compared with the Turkish students, or it may reflect job opportunities. A small survey of Australian veterinary graduates showed that just over one half (52%) were working with cats and dogs in private practice 15 years after graduating (Heath, 2007). Most government veterinary services now charge fees, with the result that extension and fieldwork have diminished (Maxwell, Costa, Layman, & Robertson, 2008).…”
Section: Demographicsmentioning
confidence: 97%